A Grammar of the Bedouin Dialects of the Northern Sinai Littoral : Bridging the Linguistic Gap between the Eastern and Western Arab World - Jong, Rudolf Erik de (Brill Book Archive Part 1, ISBN: 9789004472495., 2000)
This study offers a thorough analysis of hitherto unknown Arabic dialects spoken by bedouin tribes inhabiting the northern Sinai littoral. The author identifies five different dialect groups in the area. He combines his own extensive material with that from publications on neighbouring dialects to put this material in a larger dialect-geographical perspective. Proposing a total of 82 criteria and introducing 'partial isoglosses' to typologically measure the dialects, he convincingly shows that three dialect groups form a continuum - a 'linguistic bridge' - connecting the bedouin type of dialects spoken in the Negev and southern Jordan with the sedentary type of dialects spoken in the Nile Delta. An appendix with 77 maps completes the picture. Arabists, dialectologists, semitists and sociolinguists will welcome this study as a valuable contribution to their fields.